Strategi Pendidikan Karakter sebagai Upaya Preventif dan Kuratif untuk Mencegah Bullying terhadap Anak Usia Dini - Laili, Alifatul; Hidayah, Nurul (YASIN, 2025)
Bullying in early childhood is a serious issue that negatively impacts children's psychological, social, and academic development, manifesting in school avoidance, social withdrawal, decreased concentration, and even self-harming thoughts. This study aims to analyze strategies for preventing bullying in early childhood, identify influencing factors, and examine the role of character education as a preventive approach. A descriptive qualitative method was employed through observation, interviews, and documentation, involving school principals and classroom teachers as research subjects. Data were analyzed using the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing, with data validity strengthened through triangulation and member checking. The results indicate that character education strategies—implemented through the habituation of moral values, teacher role modeling, emotional reinforcement, parental involvement, and thematic learning are effective in preventing bullying behaviors. These strategies foster empathy, tolerance, and cooperation among children while reducing tendencies toward aggression. The study concludes that holistic integration of character education into early childhood learning is essential. The implications highlight the need for synergy among families, schools, and communities to create a safe, inclusive, and positive learning environment that supports children's overall development.